2014
DOI: 10.1002/polb.23592
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crystalline orientation and texture during solid phase die‐drawing of PP‐Talc composites

Abstract: The objective of the present work was to examine the development of crystalline orientation and texture in the polypropylene matrix of talc-filled i-PP and in unfilled i-PP with increasing draw ratio during solid-phase die-drawing at high strain rates (1 s 21 ) and a die temperature of 145 C. After drawing, the entire billet was cooled rapidly "under tension" to room temperature before releasing the billet and cutting specimens from different axial locations for analysis. Orientation distributions of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It is assumed that one of these peaks corresponds to crystals of the interconnected bridges between the lamellae and the other reflects the lamellae crystals. [28][29][30] Seguela et al [31] they reported the transition of metastable phase to more stable a-PP crystals during deformation process. They also showed that this endotherm revealed a smectic metastable phase, which was produced when a polypropylene film was extruded and rapidly cooled to room temperature.…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
“…It is assumed that one of these peaks corresponds to crystals of the interconnected bridges between the lamellae and the other reflects the lamellae crystals. [28][29][30] Seguela et al [31] they reported the transition of metastable phase to more stable a-PP crystals during deformation process. They also showed that this endotherm revealed a smectic metastable phase, which was produced when a polypropylene film was extruded and rapidly cooled to room temperature.…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
“…The applied voltage and amperage of the X-ray beam was selected to make sure it penetrated through the polypropylene film. 19 The incident beam was collimated by a 1 mm diameter collimator. The film samples were subjected to azimuthal scans with the detector positioned at 2h angles of the a(110), a(040) and a(130) crystal planes of polypropylene.…”
Section: Characterization Proceduresmentioning
confidence: 99%
“…The results of many studies have shown that composite material after inorganic filling had obvious mechanical performance improvement under the combined action of the drawing load at the free end [29,30]. Wu et al [31] studied the properties of PP/multi-wall carbon nanotube composites under the die drawing method and showed that the tensile strength increased by 550% after drawing.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [32] investigated the performance of porous tape prepared by solid-state drawn PP/Talc composites, and the results showed that the porosity increased with the increase in the drawing ratio. Rane et al [30] studied the crystal orientation and microstructure development of PP/Talc composites under different tensile ratios. As far as the current research is concerned, there are few studies on the effect of drawing process parameters on the properties of PP/inorganic particle composites.…”
Section: Introductionmentioning
confidence: 99%